2011
DOI: 10.1007/s10916-011-9732-z
|View full text |Cite
|
Sign up to set email alerts
|

A Low-cost Reader for Automatically Collecting Vital Signs in Hospitals

Abstract: Nowadays, the use of medical sensors with embedded communication modules provides accurate number reading and automatic recording. However, such readers are usually more expensive than similar devices without an embedded communication module. Further, different vendors define proprietary communication protocols and data formats for their own medical sensors. Due to the twin issues of high cost and diversity of standards, the automatic collection of patients' vital signs is not common in hospitals, meaning that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, vital sign measurement can now be automated and entered directly into an electronic patient medical record. [23][24][25][26][27] Moreover, these vital signs can be monitored remotely 27 and early warnings can be generated upon the development of abnormalities. 25 Bellomo et al 26 reported that automated vital signs monitors improved the proportion of rapid response team calls triggered by respiratory criteria, increased survival of patients and decreased the time required for vital signs measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, vital sign measurement can now be automated and entered directly into an electronic patient medical record. [23][24][25][26][27] Moreover, these vital signs can be monitored remotely 27 and early warnings can be generated upon the development of abnormalities. 25 Bellomo et al 26 reported that automated vital signs monitors improved the proportion of rapid response team calls triggered by respiratory criteria, increased survival of patients and decreased the time required for vital signs measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Manual vital sign measurement and recording is labour and time intensive. However, vital sign measurement can now be automated and entered directly into an electronic patient medical record 23–27 . Moreover, these vital signs can be monitored remotely 27 and early warnings can be generated upon the development of abnormalities 25 .…”
Section: Discussionmentioning
confidence: 99%
“…(b) Design sensible systems and scenarios, then collect data. (c) Construct data schema and perform patient activity [ 54 , 55 ].…”
Section: “Slow Well-being Gardening” Frameworkmentioning
confidence: 99%
“…Medical sensors, such as electrocardiograms, pulse oximeters, sphygmomanometers and arrhythmia detectors, are widely used to monitor vital signs of patients [21]. Pulse oximeter is a non-invasive device which does not emit heat or radiation.…”
Section: Pulse Oximeter and Its Operation Principlementioning
confidence: 99%